1995
DOI: 10.1097/00003246-199510000-00012
|View full text |Cite
|
Sign up to set email alerts
|

T-lymphocyte subsets in acute illness

Abstract: Acute illness alone, in the absence of HIV infection, can be associated with profound decreases of T-lymphocyte populations. This problem is unpredictable and does not correlate with severity of illness, predicted mortality rate, or actual mortality rate. No conclusions regarding HIV serostatus or survival can be made based on single measurements of T-cell concentrations in acutely ill hospitalized patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
18
0
2

Year Published

2000
2000
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 17 publications
2
18
0
2
Order By: Relevance
“…This decrease of CD4 + /CD8 + T lymphocyte ratio was highly significant compared to acute cases (P = 0.038). This shows that low CD4 + T lymphocyte counts are associated with a variety of conditions in viral infections [35]. These findings were in corroboration with study carried out on patients with cervical intraepithelial neoplasia and invasive cancer revealed a decrease in CD4 cells with a relative increase in CD8 cell count, leading to a considerable reduction in the CD4/CD8 cell ratio [36].…”
Section: Discussionsupporting
confidence: 77%
“…This decrease of CD4 + /CD8 + T lymphocyte ratio was highly significant compared to acute cases (P = 0.038). This shows that low CD4 + T lymphocyte counts are associated with a variety of conditions in viral infections [35]. These findings were in corroboration with study carried out on patients with cervical intraepithelial neoplasia and invasive cancer revealed a decrease in CD4 cells with a relative increase in CD8 cell count, leading to a considerable reduction in the CD4/CD8 cell ratio [36].…”
Section: Discussionsupporting
confidence: 77%
“…41 percent had CD4 levels below 400, and 29 percent were below 300. The CD4/CD8 ratio, thought to be a marker of HIV infection, was less than one in 16 percent [16]. Secondly, individuals have been identified with low levels of CD4 without HIV infection, both associated with opportunistic infections and also when asymptomatic [17]–[19].…”
Section: Discussionmentioning
confidence: 99%
“…Because there are various non-HIV-related causes of CD4 decline such as acute illness or CD4-lowering treatments like trimethoprim-sulfamethoxazole, chemotherapy or interferon. 8,24 Physiologic variation can also lead to a transient CD4 decline. One study reported physiologic CD4 variation around a median of 119 cells/μL ranged from 35 to 395 cells/μL over 2 weeks.…”
Section: Discussionmentioning
confidence: 99%